Membangun Karakter Siswa Melalui Keteladanan Guru - Muhammad Fadlan Fadillah Arif; Mhd Aris Saputra Harahap; Panji Kesuma (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Character formation in students is a crucial aspect of modern education, with teachers serving as primary role models. This study aims to analyze the impact of teacher exemplarity on student character development and identify effective strategies for its implementation. Using a qualitative approach, the study combines literature analysis with in-depth interviews of 15 teachers and 30 students from various educational levels. Results indicate that teacher exemplarity significantly impacts student character formation, particularly in aspects of integrity, discipline, empathy, and work ethic. Effective strategies include consistency between words and actions, positive attitudes in facing problems, and respectful interactions. Key challenges include social pressure and time constraints. The research concludes that teacher exemplarity plays a vital role in creating a conducive learning environment and shaping positive student character. These findings imply the need for enhanced teacher professional development programs focusing on exemplarity aspects and the integration of character values into school curricula.